Man in the Modern Philosophy - Subatavičiūtė, Angelė (Problemos, 1989)
The solution of the problem of free will has methodological significance in explaining all questions of man and eventually of his personality. From this point of view man and his social life are analysed in the philosophical systems of R. Descartes, B. Spinoza and the materialists of the 18th century. The article indicates that the formulation of the problem of personality is more substantiated in the philosophy of R. Descartes ant B. Spinoza than in the ethical theories of the materialists of the 18th century.